Facial Papulopustular Eruption during the COVID-19 Pandemic in Patients Treated with EGFR Inhibitors - Eleonora De Luca; Pietro Sollena; Lucia Di Nardo; Ettore D'Argento; Emanuele Vita; Giampaolo Tortora; Ketty Peris (Hindawi Limited, 2024)
Papulopustular rash (PPR) is the most frequent cutaneous adverse event during treatment with epidermal growth factor receptor inhibitors (EGFRis). Although often mild in severity, it can impair patients' quality of life and may also be a reason for discontinuing or changing the dose of the antineoplastic treatment. During COVID-19 pandemics, the use of surgical masks drastically increased and it had an impact on the face skin microenvironment, favoring the worsening of dermatological pathologies. We reported the relapse of PPR in patients treated with EGFR inhibitors who consistently wore face masks (>6 hours/day). All the patients developed the PPR within 6 months of starting mask use. Compared to the PPR occurred previously, after mask use, the skin eruption was more severe and affected mainly those regions of the face which came into contact with the mask. Patients received topical or systemic treatment, obtaining complete response in 65.7% of the cases. The establishment of an early treatment for the PPR allows continuing the oncologic treatment, without any suspension which could result in a decreased oncologic outcome. In conclusion, when using these devices, it is recommended to use special precautions, particularly in oncologic patients, by using a daily prophylactic skincare and replacing masks regularly with regular and frequent breaks.